2022
DOI: 10.1093/bjsopen/zrab130
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of selection criteria for liver transplantation in patients with hepatocellular carcinoma: a network meta-analysis

Abstract: Background Patients with hepatocellular carcinoma (HCC) are selected for transplantation if they have a low tumour burden and low risk of recurrence. The morphometric Milan criteria have been the cornerstone for patient selection, but dynamic morphological and biological tumour characteristics surfaced as an encouraging tool to refine the selection of patients with HCC and to support the expansion of the Milan criteria. The outcomes of the most prevalent models that select patients with HCC f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…There have been efforts to extend the Milan criteria as other treatment options are lacking and the survival rates of patients transplanted outside the Milan criteria are considerable 15 16 17 18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been efforts to extend the Milan criteria as other treatment options are lacking and the survival rates of patients transplanted outside the Milan criteria are considerable 15 16 17 18 .…”
Section: Discussionmentioning
confidence: 99%
“…However, due to organ shortages, DDLT is still reserved for patients with the most favorable postoperative outcome, which is widely accepted to be HCCs inside the Milan criteria 18 . In our patient, the impressive size of the HCC (18 cm diameter) has excluded her from any established transplantation criteria for DDLT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many selection criteria models have attempted to estimate outcomes based on pre-LT tumor size, number, and biomarker thresholds [12–15]. A recently published meta-analysis compared post-LT outcomes between the Milan, UCSF, Up-to-Seven (UPTS), French AFP (FAFP), and MetroTicket 2.0 (MT2) models [16 ▪▪ ]. They found that the MT2 model (which incorporates tumor number and size as well as AFP level) had the highest 1-, 3-, and 5-year DFS, and within MC patients had the highest 5-year overall survival rates.…”
Section: Surgical Therapiesmentioning
confidence: 99%